Diagnostic Value of Next-Generation Sequencing in an Unusual Sphenoid Tumor. (7th May 2014) - Jamshidi, Farzad; Pleasance, Erin; Li, Yvonne; Shen, Yaoqing; Kasaian, Katayoon; Corbett, Richard; Eirew, Peter; Lum, Amy; Pandoh, Pawan; Zhao, Yongjun; Schein, Jacqueline E.; Moore, Richard A.; et al.
Abstract: Extraordinary advancements in sequencing technology have made what was once a decade-long multi-institutional endeavor into a methodology with the potential for practical use in a clinical setting. We therefore set out to examine the clinical value of next-generation sequencing by enrolling patients with incurable or ambiguous tumors into the Personalized OncoGenomics initiative at the British Columbia Cancer Agency whereby whole genome and transcriptome analyses of tumor/normal tissue pairs are completed with the ultimate goal of directing therapeutics. First, we established that the sequencing, analysis, and communication with oncologists could be completed in less than 5 weeks. Second, we found that cancer diagnostics is an area that can greatly benefit from the comprehensiveness of a whole genome analysis. Here, we present a scenario in which a metastasized sphenoid mass, which was initially thought of as an undifferentiated squamous cell carcinoma, was rediagnosed as an SMARCB1 -negative rhabdoid tumor based on the newly acquired finding of homozygous SMARCB1 deletion. The new diagnosis led to a change in chemotherapy and a complete nodal response in the patient. This study also provides additional insight into the mutational landscape of an adult SMARCB1 -negative tumor that has not been explored at a whole genome and transcriptome level. Abstract : The authors report the case of a patient for whom whole genome sequencing was instrumental in assisting in the correct diagnosis of the tumor based on the finding of homozygous SMARCB1 loss. This resulted in a switch in chemotherapy protocol, leading to diminution of the distant metastases. They conclude that cancer diagnostics is an area that can greatly benefit from the comprehensiveness of a whole genome analysis.